Effects of litter chemical traits and species richness on soil carbon cycling changed over time - Yang, Hongling; Li, Yulin; Zhan, Jin; Bao, Chelmeg; Luo, Yongqing (Frontiers in Environmental Science, 2022)
Litter decomposition is the main driver of nutrient cycling process in terrestrial ecosystems. Afforestation completely altered vegetation composition and litter species, disrupting the long-term carbon balance in grassland ecosystem. However, there is a lack of understanding of how litter mixing effect (LME) affects soil carbon cycling in afforested ecosystem. Here, we investigated the effects of litter richness and quality of tree, shrub, and grass species and their litter mixture on soil CO2 fluxes. The results showed that cumulative soil CO2 flux in the early stage (1-28 days) was 1.75 times higher than that in the late stage (29-113 days), indicating litter decomposition was intensive at first and then decreased with time. Soil carbon flux changed with decomposition stages. In the early-stage of decomposition, soil CO2 flux increased with the concentrations of litter carbon, nitrogen and condense tannin. In the late phase of decomposition, all litter chemical traits were negatively related to the soil carbon flux. Additionally, plant litter richness was negatively correlated to early-stage soil CO2 flux, whereas it was positively related to late-stage soil carbon flux. Our results provide evidence that long-term carbon balance in grassland ecosystems was interrupted by afforestation, and the dominant litter chemical traits that controlling soil carbon cycling changed over time.